Orações consecutivas finitas em Português Europeu: uma análise sintática - Brito, Ana Maria; Matos, Gabriela (Revista da Associação Portuguesa de Linguística, 2016)
In this paper we analyse antecedent and free consecutives. In consecutives with overt antecedents, we adopt the split degree hypothesis of Corver (1993, 1997a, b 2013), which has the advantage of separating determiner-like degree word and quantifier-like words. We also adopt Kennedy’s (1997, 1999) and Corver’s (2013) hypotheses that consecutive CPs are adjuncts that act as modifiers of a DegP, which form a unit with the degree/quantifying word at the level of LF. This analysis is extended to free consecutive clauses. We claim that in free consecutives the gradable expression is an elided constituent included in the sentence that contains the consecutive CP, whose content must be recovered by (an element of) the sentence to which it is paratactically related.